Nintendo Wii Game in Balance Stroke Rehabilitation: A Narrative Review - Javid Mostamand; Ehsan Ghasemi; Narges Yousefi (Vesnu Publications, 2020)
Introduction: Stroke is known as the second cause of disability in adults, which finally leads to disabilities such as movement impairments, cognitive disorders, and speech disorders. Balance disturbance and neuromuscular incoordination are the most common adverse effects of stroke. Using virtual reality systems are considering as a standard treatment method in neurologic disorders especially in stroke. Nintendo Wii games let patients do different tasks in miscellaneous environment. Materials and Methods: Medline, PEDro, and Cochrane library databases were searched until 2018. Articles that used Nintendo Wii in treatment of balance disturbance in any phase of stroke were selected. Results: Among 21 studies, 8 were selected. In these studies, balance test was used as main outcome measure. Improvement of static balance was shown in 2 studies. In 3 of them, balance improved significantly in intervention group rather than control group. Moreover, in 3 other studies, improvement process was reported in patients with stroke, but the results were not significant. Conclusion: The result of all included studies showed positive effect of Nintendo Wii game on balance in patients with stroke.